Synthesis and Characterization of Tin Iv Oxide (Sno2) Nanoparticles for Energy Applications - Nuamah, R. A. (University of Ghana, 2016)
Electrochemical capacitors (ECs) or Supercapacitors (SCs) are energy saving devices which have excellent properties that include high power density, long cycle life, low temperature sensitivity and low maintenance cost. However these devices have lower energy densities than conventional batteries. To improve on its energy density, SnO2 which is a metal oxide was considered as an electrode material because of its chemical inertness and thermal stability. SnO2 nanoparticles were synthesized using the hydrothermal and water-in-oil microemulsion techniques. Well crystalline particles with different morphologies and crystallite size in the range of 2nm to 10nm were obtained by using Urea and Soduim Borohydride as reducing agents, Dioctyl Sulfosuccinate sodium salt (AOT) and Cetyl Trimethyl ammonium bromide (CTAB) as the surfactants in the hydrothermal techniques. X-ray diffractometry, Scanning Electron microscopy, Energy Dispersive X-ray spectroscopy and Fourier Transform Infrared spectroscopy revealed the presence of tin oxide (SnO2). The electrochemical properties were investigated using cyclic voltammetry, electrochemical impedance spectroscopy and potentiostatic charge-discharge in aqueous KOH electrolyte. The SnO2 electrode material showed properties as a pseudocapacitor with a maximum capacitance value of 1.6 Fg-1 at a scan rate of 5 mVs-1, an efficiency of 52 % at a current of 1mA and a maximum capacitance retention of about 40% after 10 cycles at a current of 1 mA. From the results obtained it can be concluded that Sodium borohydride is a better reducing agent in the synthesis of SnO2 nanoparticles. Also, although the crystallite size of the SnO2 particles were small they exhibited very low pseudocapacitance as a result of the low conductivity of the nanoparticles and the lack of electrochemical active sites. To improve on University of Ghana http://ugspace.ug.edu.gh v the capacitance of the SnO2 nanoparticles, conductive carbon can be added and composite SnO2 composite materials with carbonaceous materials can also be an alternative
Thesis (MPhil) - University of Ghana,2016
Keywords: Synthesis; Tin Iv Oxide (Sno2) Nanoparticles; Energy; Characterization